We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
158
2
avatar

Let \(S = \frac{1}{2^3} + \frac{1}{4^3} + \frac{1}{6^3} + \dotsb\) and \(T = \frac{1}{1^3} + \frac{1}{3^3} + \frac{1}{5^3} + \dotsb\). Find \(S/T\).

 Feb 18, 2019

Best Answer 

 #1
avatar
+1

S=sumfor(n, 1, 1000, 1/(2*n)^3)=0.1502571129
T-sumfor(n, 1, 1000, 1/((2*n- 1 )^3))=1.05179979

S/T =0.1502571129 / 1.05179979

S/T = 1 / 7

 Feb 18, 2019
 #1
avatar
+1
Best Answer

S=sumfor(n, 1, 1000, 1/(2*n)^3)=0.1502571129
T-sumfor(n, 1, 1000, 1/((2*n- 1 )^3))=1.05179979

S/T =0.1502571129 / 1.05179979

S/T = 1 / 7

Guest Feb 18, 2019
 #2
avatar+23313 
+4

help

Let 

\(\large{S = \dfrac{1}{2^3} + \dfrac{1}{4^3} + \dfrac{1}{6^3} + \dotsb}\)

and
\(\large{T = \dfrac{1}{1^3} + \dfrac{1}{3^3} + \dfrac{1}{5^3} + \dotsb}\).
Find

\(\large{\dfrac{S}{T}}\)

 

1.

\(\mathbf{S+T =\ ?}\)

\(\begin{array}{|rcll|} \hline S+T &=& \left(\dfrac{1}{2^3} + \dfrac{1}{4^3} + \dfrac{1}{6^3} + \dotsb \right) +\left(\dfrac{1}{1^3} + \dfrac{1}{3^3} + \dfrac{1}{5^3} + \dotsb \right) \\ S+T &=& \color{red}{\dfrac{1}{1^3} + \dfrac{1}{2^3} + \dfrac{1}{3^3} + \dfrac{1}{4^3} + \dfrac{1}{5^3} + \dfrac{1}{6^3} + \dotsb} \\ \hline \end{array}\)

 

2.

\(\mathbf{\dfrac{S}{T} =\ ?} \)

\(\begin{array}{|rcll|} \hline S &=& \dfrac{1}{2^3} + \dfrac{1}{4^3} + \dfrac{1}{6^3}+ \dfrac{1}{8^3}+ \dfrac{1}{10^3} + \dotsb \\ &=& \dfrac{1}{(2\cdot 1)^3} + \dfrac{1}{(2\cdot 2)^3} + \dfrac{1}{(2\cdot 3)^3}+ \dfrac{1}{(2\cdot 4)^3}+ \dfrac{1}{(2\cdot 5)^3} + \dotsb \\ &=& \dfrac{1}{2^3 1^3} + \dfrac{1}{2^3 2^3} + \dfrac{1}{2^3 3^3}+ \dfrac{1}{2^3 4^3}+ \dfrac{1}{2^3 5^3} + \dotsb \\ &=& \dfrac{1}{2^3} \underbrace{ \left(\color{red}{\dfrac{1}{1^3} + \dfrac{1}{2^3} + \dfrac{1}{3^3}+ \dfrac{1}{4^3}+ \dfrac{1}{5^3} + \dotsb} \right) }_{=S+T} \\ &=& \dfrac{1}{2^3}(S+T) \\\\ S &=& \dfrac{1}{8}(S+T) \quad | \quad \cdot 8 \\ 8S &=& S+T \quad | \quad -S \\ 7S &=& T \quad | \quad :7 \\ S &=& \dfrac{T}{7} \quad | \quad:T \\ \mathbf{\dfrac{S}{T}} & \mathbf{=} & \mathbf{\dfrac{1}{7}} \\ \hline \end{array}\)

 

laugh

 Feb 19, 2019

7 Online Users

avatar